Pelatihan dan Pendampingan Implementasi Deep Learning bagi Guru Sekolah Dasar di Kecamatan Cilawu - Widdy Sukma Nugraha; Muhammad Nurjamaludin; Eko Fajar Suryaningrat; Abdul Hakim; Dani Gunawan; Rajji Koswara Adiredja; Lutfi Asyari (IPI Press, 2026)
Deep Learning is a learning approach that emphasizes conceptual understanding, higher-order thinking skills, and the integration of knowledge with real-life contexts. However, the implementation of this approach at the elementary school level still faces various challenges, particularly related to teachers’ conceptual understanding and pedagogical skills. This Community Service program aimed to enhance the competencies of elementary school teachers in Cilawu District, Garut Regency, in implementing Deep Learning effectively and contextually. The program employed workshop-based training, continuous mentoring, reflective discussions, and hands-on practice in developing Deep Learning–oriented instructional plans. The participants were elementary school teachers from several schools in Cilawu District. The results indicated an improvement in teachers’ understanding of Deep Learning principles, their ability to design learning activities that promote critical and collaborative thinking, and their readiness to implement the approach in classroom practice. Furthermore, sustained mentoring supported teachers in addressing practical challenges during implementation. Therefore, this program contributes positively to improving the quality of elementary education and strengthening teachers’ professional competence.